Pumpkin Seeds and Heart Health: A Comprehensive Review of Their Role in Cardiovascular Disease Prevention and Management: Pumpkin Seeds and Heart Health - Adnan, Minahil; Javed, Farah; Mallhi, Iftikhar Younis; Naseem, Chanda; Iqbal, Muhammad Jawad; Azeem, Ayesha; Nisar, Tehreem; Kamran, Musharib Razi; Kamran , Yashal Razi; Zulfiqar , Taliya (Pakistan Journal of Health Sciences, 2025)
Cardiovascular Diseases (CVDs) remain a major global health concern, with an increasing prevalence requiring urgent preventive strategies. Diet and lifestyle play a crucial role in CVD development, emphasizing the need for healthy food interventions. To explore the potential cardioprotective benefits of pumpkin seeds (Cucurbita spp.) and their bioactive compounds in promoting cardiovascular health. Relevant literature was reviewed to evaluate the macronutrient and micronutrient profile of pumpkin seeds, as well as their bioactive compounds. Study Design: A comprehensive review of the nutritional composition and functional properties of pumpkin seeds was conducted, focusing on their role in cardiovascular disease prevention. Key components, including linolenic acid, phytosterols, antioxidants, and pumpkin seed oil, were analyzed for their potential impact on cardiovascular health. Pumpkin seeds are rich in proteins, carbohydrates, and unsaturated fatty acids, along with essential micronutrients such as zinc, phosphorus, magnesium, potassium, and selenium. Linolenic acid in pumpkin seeds offers protective effects against CVDs, diabetes, and certain cancers. Phytosterols contribute to lowering LDL cholesterol levels, while their strong antioxidant properties help reduce oxidative stress, lower blood pressure, and prevent arteriosclerosis. Pumpkin seed oil, rich in magnesium, enhances Nitric Oxide (NO) production, supporting vascular function and aortic protection. Given the increasing focus on plant-based diets for chronic disease prevention, regular consumption of pumpkin seeds may provide significant benefits in improving cardiovascular health. Further research and clinical trials are recommended to establish optimal dietary intake guidelines for maximizing their protective effects.